The Impact of Saharan Dust on the North Atlantic Circulation - Martinez Avellaneda, Nidia (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2010)
The erosion of Saharan soil is the World's largest annual source of mineral dust aerosols, resulting in a deposition of more than 40% of the global atmospheric dust into the North Atlantic. By changing the atmospheric opacity, mineral dust can alter the shortwave radiative forcing at the surface of the ocean, altering the ocean mixed layer heat budget and therefore affecting the sea surface temperature (SST), which plays an important role in the regional and global climate. Moreover, changes of the total amount of energy received at the ocean surface have an impact on the ocean circulation. In this thesis we combine several satellite observations, in-situ radiation measurements, a one-dimensional mixed layer model of the ocean, and various versions of a three-dimensional general ocean circulation model, to study the impact of Saharan dust on the circulation and transport of properties in the North Atlantic. A buoyancy source generated by realistic dust-induced shortwave flux anomalies is imposed in the eastern North Atlantic and the differences between this simulation and an unperturbed one are investigated in terms of the ocean dynamical adjustment and changes in the Atlantic Meridional Overturning Circulation (AMOC) and Meridional Heat Transport (HT). A joint analysis of aerosol optical depth retrievals from the MODIS sensor and SST from the TMI sensor for the period 2000-2006 shows a decrease in SST of 0.2° to 0.4°C simultaneously with, or shortly after, strong dust outbreaks, which is consistent with an independent estimate of SST decrease simulated by a local 1D mixed layer model. A comparison between observed TMI SST fields and simulated SSTs with an eddy-permitting model of the North Atlantic suggests a local cooling of about 0.5°C on sub-seasonal to interannual time-scales. A regression analysis suggests that about 9% of SST variance could be explained by dust-induced cooling in this region which is not represented in existing AVHRR sensor SST fields nor represented in surface heat fluxes from current ...